КРИМІНАЛІСТИЧНА ХАРАКТЕРИСТИКА ЗЛОЧИНІВ, ПОВ’ЯЗАНИХ З ПОРУШЕННЯМИ ПРАВИЛ ОХОРОНИ ПРАЦІ ТА БЕЗПЕКИ ВИРОБНИЦТВА ПІД ЧАС БУДІВНИЦТВА - Запотоцький, Андрій Петрович (SUPREMANCE OF LAW, 2017)
The article is devoted to the forensic description ofcrimes related to violations of the rules of labor protection and safety of production during construction is considered, and its elements are described. Much attention is given to the study of legislation, literary sources, the results of the generalization of investigative and judicial practice. The important role of the method and the typical trace pattern of the commission of this category of crimes is determined.